2017
DOI: 10.1093/jrr/rrx060
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a prognostic scoring system based on the systemic inflammatory and nutritional status of patients with locally advanced non-small-cell lung cancer treated with chemoradiotherapy

Abstract: Systemic inflammation and poor nutritional status have a negative effect on the outcomes of cancer. Here, we analyzed the effects of the pretreatment inflammatory and nutritional status on clinical outcomes of locally advanced non-small-cell lung cancer (NSCLC) patients treated with chemoradiotherapy. We retrospectively reviewed 89 patients with locally advanced NSCLC treated with chemoradiotherapy between July 2006 and June 2013. Serum C-reactive protein (CRP) was assessed as an inflammatory marker, and serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…6,[12][13][14][15][16][17][18][19] In studies covering both resectable and metastatic lung cancers, the worst outcomes were observed in underweight patients as defined by having a body mass index (BMI) less than 18.5 kg/m 2 . 6,[12][13][14][15][20][21][22][23][24][25][26][27][28][29] Being severely underweight may be an indicator of cancer cachexia, which is a well-described marker of poor outcome on cancer mortality. [30][31][32][33][34][35] Weight in the years before lung cancer diagnosis has also been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…6,[12][13][14][15][16][17][18][19] In studies covering both resectable and metastatic lung cancers, the worst outcomes were observed in underweight patients as defined by having a body mass index (BMI) less than 18.5 kg/m 2 . 6,[12][13][14][15][20][21][22][23][24][25][26][27][28][29] Being severely underweight may be an indicator of cancer cachexia, which is a well-described marker of poor outcome on cancer mortality. [30][31][32][33][34][35] Weight in the years before lung cancer diagnosis has also been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the tissue marker, serum markers are preponderance, which is easily acquisitive and convenient monitoring. Recent studies found some serum markers, which reflected systemic inflammation and nutritional status, affected the prognosis of NSCLC 15,16 . For example, NSCLC patients in the early stage, especially those with pulmonary fibrosis, low preoperative serum ALB level is an unfavorable indicator regarding postoperative survival 17 …”
Section: Discussionmentioning
confidence: 99%
“…and follow-up in lung cancer patients and offers an elegant way to simultaneously assess sarcopenia by calculating the skeletal muscle mass index (5,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%